Assessment of the functional state of boxers by complex results of rhythmocardiographic analysis - Shchedrina, Y. A.; Melnikov, D. S.; Chernozipunnikova, E. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the functional state of boxers using complex indicators calculated on the basis of HRV, with an assessment of the feasibility of their use for qualified athletes.